Innovative approaches to fashion services and sustainability - Bernardes, João Pedro (2017)
This paper explores the creation and acceptance of an innovative service called 0KG, that is inspired by the ‘slow fashion movement’, and that focuses on the question: "are people willing to use second-hand clothing and/or leased when traveling?". 0KG is a rental service for the day-to-day, business, and also cultural clothing. The creation and development of this service happened through the use of a design thinking methodology: 9 steps framework by Kees Dorst. Regarding its validation, it was achieved with a focus group with people of interest. Finally, the paper culminates with the positive response to the problem.